TMPRSS11D and TMPRSS13 Activate the SARS-CoV-2 Spike Protein - Kishimoto, Mai; Uemura, Kentaro; Sanaki, Takao; Sato, Akihiko; Hall, William W.; Kariwa, Hiroaki; Orba, Yasuko; Sawa, Hirofumi; Sasaki, Michihito (Viruses, 2021)
Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) utilizes host proteases, including a plasma membrane-associated transmembrane protease, serine 2 (TMPRSS2) to cleave and activate the virus spike protein to facilitate cellular entry. Although TMPRSS2 is a well-characterized type II transmembrane serine protease (TTSP), the role of other TTSPs on the replication of SARS-CoV-2 remains to be elucidated. Here, we have screened 12 TTSPs using human angiotensin-converting enzyme 2-expressing HEK293T (293T-ACE2) cells and Vero E6 cells and demonstrated that exogenous expression of TMPRSS11D and TMPRSS13 enhanced cellular uptake and subsequent replication of SARS-CoV-2. In addition, SARS-CoV-1 and SARS-CoV-2 share the same TTSPs in the viral entry process. Our study demonstrates the impact of host TTSPs on infection of SARS-CoV-2, which may have implications for cell and tissue tropism, for pathogenicity, and potentially for vaccine development.